2019
DOI: 10.1186/s13071-019-3722-2
|View full text |Cite
|
Sign up to set email alerts
|

Vector competence is strongly affected by a small deletion or point mutations in bluetongue virus

Abstract: Background: Transmission of vector-borne virus by insects is a complex mechanism consisting of many different processes; viremia in the host, uptake, infection and dissemination in the vector, and delivery of virus during bloodfeeding leading to infection of the susceptible host. Bluetongue virus (BTV) is the prototype vector-borne orbivirus (family Reoviridae). BTV serotypes 1-24 (typical BTVs) are transmitted by competent biting Culicoides midges and replicate in mammalian (BSR) and midge (KC) cells. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Reoviridae is a very successful family of segmented dsRNA viruses, having wide host ranges across various econiches. The family's repertoire of evolutionary strategies also includes deletion [82,83], gene duplication and concatemerisation [9,84,85]. These strategies were also observed previously in aquareoviruses [86], rotaviruses [87], phytoreoviruses [88] and even in a cross-family heterologous recombinant virus containing reovirus genomic components [89].…”
Section: Discussionsupporting
confidence: 62%
“…Reoviridae is a very successful family of segmented dsRNA viruses, having wide host ranges across various econiches. The family's repertoire of evolutionary strategies also includes deletion [82,83], gene duplication and concatemerisation [9,84,85]. These strategies were also observed previously in aquareoviruses [86], rotaviruses [87], phytoreoviruses [88] and even in a cross-family heterologous recombinant virus containing reovirus genomic components [89].…”
Section: Discussionsupporting
confidence: 62%
“…This reduction of viremia not only prevents the development of clinical signs in the immunized animals but may also reduce viral acquisition by Culicoides bites. Experimental infections of Culicoides sonorensis with BTV-11 and BTV-1 infected blood showed that the efficiency of infection of midges was dose-dependent and the 50% Midge Alimentary Infective Dose (MAID50) was estimated to a blood meal titer around 2 × 10 5 TCID50/mL [ 62 , 63 ]. In the case of BTV-4M, a virus titer between 10 5 and 10 6 TCID50 is enough to ensure BTV infection rates of 100% for C. imicola and ~83% for C. obsoletus / scoticus [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the viremia was not abrogated in the immunized sheep, the titers of virus found in two out of three sheep were 10 3 PFU/ml or lower. Experimental infections of Culicoides sonorensis with BTV-11 and BTV-1 infected blood showed that the efficiency of infection of midges was dose-dependent and the 50% Midge Alimentary Infective Dose (MAID 50 ) was roughly calculated to a blood meal titer of ±2 × 10 5 and ±10 6 Median Tissue Culture Infectious Dose (TCID 50 )/ml for BTV-11 and BTV-1, respectively 43 , 44 . According to these experimental infections, the level of virus detected in the blood of the MVA-GnGc-NS1-vaccinated sheep was 200 times lower than the minimal dose required for the insect vector infection, not being sufficient to infect midges and then avoiding the transmission of the virus.…”
Section: Discussionmentioning
confidence: 99%